WAYS TO IMPROVE THE LEGAL REGULATION OF ADMINISTRATIVE PROCEDURES IN LOCAL SELF-GOVERNMENT BODIES IN UKRAINE - Malysh, Oleksandr (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2025)
The purpose of the article is aimed at studying ways to improve the regulatory regulation of administrative procedures in local self-government bodies in Ukraine. Research methods: the chosen topic of scientific research requires the use of various scientific methods and approaches to obtain qualitative results. Therefore, the following research methods were used to solve the tasks: analysis; system method; analytical, etc. Results: improving the legal regulation of administrative procedures in local self-government bodies in Ukraine is a necessary step to increase legal certainty, ensure effective judicial protection and strengthen constitutional guarantees of individuals. Discussion: the administrative procedure is of key importance for local self-government, since, on the one hand, it determines the procedure for the exercise of their powers by local self-government bodies, and on the other hand, it serves as a tool for ensuring the rights, freedoms and legitimate interests of individuals and legal entities. The study of the issues of regulatory regulation of administrative procedures in the field of local councils’ activities is conditioned by the need for an in-depth analysis and search for effective areas of improvement of domestic legislation regulating the regulation of administrative procedures in local self-government bodies in Ukraine, including the procedure for adopting and appealing against regulatory legal acts of local self-government bodies. In addition, the problem is of considerable importance both in the scientific and practical dimensions, as it requires a study of the effectiveness of existing mechanisms, the identification of gaps in regulatory regulation, as well as an assessment of the compliance of national norms with international standards in the field of protection of citizens’ rights and the development of local democracy. The implementation of an integrated approach within the framework of this work will outline the main shortcomings of the current system, formulate proposals for improving legal regulation and contribute to the formation of effective administrative practice at the local level. In general, modern trends in the development of public administration require ensuring openness, transparency and efficiency of local self-government bodies. One of the prerequisites for achieving this is a clear and systematic regulatory regulation of administrative procedures.